2013
DOI: 10.3748/wjg.v19.i15.2319
|View full text |Cite
|
Sign up to set email alerts
|

Effect of biliary drainage on inducible nitric oxide synthase, CD14 and TGR5 expression in obstructive jaundice rats

Abstract: ID could be attributed to the regulatory function of activation of KCs and release of inflammatory mediators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Although there are various different rat models to choose from, researchers do not seem to accept most of them. In newly published articles, choledochoduodenostomy was still the prior internal drainage technique for many researchers [ 1 17 18 19 20 21 ]. However, choledochoduodenostomy was not suitable in some studies because of high mortality and morbidity rates and poor stability [ 4 5 9 16 22 23 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there are various different rat models to choose from, researchers do not seem to accept most of them. In newly published articles, choledochoduodenostomy was still the prior internal drainage technique for many researchers [ 1 17 18 19 20 21 ]. However, choledochoduodenostomy was not suitable in some studies because of high mortality and morbidity rates and poor stability [ 4 5 9 16 22 23 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, the models of obstructive jaundice (OJ) and its reversal are frequently used in many experimental studies such as on the benefits and risks of preoperative internal and external drainage, short-term and long-term outcomes after surgery, and metabolism changes in liver and digestive tract [ 1 2 3 4 ]. An ideal model for OJ and its reversal should be technically easy, stable during the study period, and associated with low mortality and morbidity rates.…”
Section: Introductionmentioning
confidence: 99%
“…Internal drainage is more physiological than external drainage, as the enterohepatic circulation of bile is maintained. The benefits of internal drainage have been demonstrated in a series of animal experiments conducted by our team concerning internal and external drainage for the management of obstructive jaundice [40][41][42]. Our results indicated that internal drainage was superior to external drainage in restoring the damaged intestinal barrier, inhibiting bacterial translocation and reducing expression of inflammatory factors.…”
Section: Discussionmentioning
confidence: 67%
“…MOJ patients are in a severe state of immunological stress during which time inflammatory cytokines are released and immune factors are consumed. Hence cellular-based immune function is decreased (8) and the immune system is inhibited (9)(10)(11). The changes in immune functions of patients are one of the key factors leading to high rates of complications and mortality which affect prognosis (12).…”
Section: Discussionmentioning
confidence: 99%